The Gambia : 2003 Article IV Consultation-Staff Report; Report on Noncomplying Disbursements and Recommendation for Corrective Action; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2003 Article IV Consultation highlights that economic performance of The Gambia deteriorated substantially in 2002-03. A collapse of the groundnut harvest in 2002 led to a contraction of real GDP by 3 percent while also affecting export revenues in 2003. At the same time, poor execution of monetary and fiscal policy, reflecting serious deficiencies in governance, caused the exchange rate to depreciate and inflation to surge. In 2003, the fiscal deficit is estimated to have declined to 6.0 percent of GDP, compared with a budget target of 4.5 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet